P215 Sharing the journey; public and commissioner experiences in developing e-service pathways in sexual health. (8th June 2017) - Reid, Simon; Clarke, Jan; Mezzone, Jane; O'Sullivan, Jonathan; Murchie, Martin
Abstract : Introduction: The London e-service is an innovative online digital health solution including: Health promotion and education; risk assessment and triage process to access self-sampling kits; provision of self-sampling kits in clinic and online; diagnostics; remote treatment for uncomplicated chlamydia; results management and partner notification. Methods: Over 5000 service users were engaged through waiting room and online surveys, interviews and public groups. There was an appetite for an online service in some segments of the population. Clinicians and commissioners worked collaboratively to develop the e-service pathway. The vision was for a high quality health pathway where the service user seamlessly travels between appropriate providers. The pathway development factored in: service user choice; clear referral pathways; protocols for safeguarding; enhanced results management and partner notification; appropriate treatment. Results: 27 boroughs participated in the collaborative procurement of the London e-service. The integration of the e-service and sexual health clinics remains a critical success factor. The pathway focuses on 2 main areas of interaction between providers: 1) The e-service 'offer' in a clinical environment; a specialist behaviour change company is working with the e-service and providers to develop channel shift resources. This is backed by a clinical service specification with associated KPIs. 2) Ensuring appropriate access to service user results and case history. This requires data sharing agreements and innovative technology solutions. The pathway was further finessed through the negotiation phase, with e-service bidders suggesting additional commercial solutions. Discussion: Can an e-service help improve access, user experience, outcomes and manage resources?